SYSTEMATIC REVIEW AND META-ANALYSIS OF SMOKING, INACTIVITY, AND DIET ASSOCIATED WITH ELDERLY HYPERTENSION: Merokok, Aktivitas Fisik, dan Pola Diet dengan Hipertensi pada Lansia: Sistematik Review dan Meta Analisis - Nuraisyah, Fatma; Irjayanti, Apriyana; Irmanto, Maxsi; Noorkhalisah, Noorkhalisah (Jurnal Berkala Epidemiologi, 2025)
Background:The condition of the elderly ca n affect blood pressure because they are unable to balance psychologically and physiologically. Lifestyle can affect risk factors for hypertension. Aims to examine lifestyle risk factors for the incidence of hypertension in the elderly with a systematic review and meta-analysis. Method: Eight electronic databases, namely: PubMed, Science PubMed, Science Direct, NCBI, ProQuest, and EBSCO Journals Online, were searched for studies published in English from 2017 to December 2023. Joanna Briggs Institute (JBI), Meta-Analysis of Statistics Assessment and review instrument for data extraction, and quality assessment. Smoking, physical activity, a diet with hypertension in the elderly and analysed using the Review Manager 5.3 application. Of a total of 3411 articles, 8 were included and analysed. Results: We identified 8 articles, and the results were statistically significant physical activity (AOR= 1.04; 95% CI= 0.70 to 1.54; p= 0.860) and not dieting (AOR= 1.37; 95% CI= 1.17 -1.61; p<0.001) are risk factors for hypertension in the elderly. Conclusion: Physical activity and not dieting are risk factors for hypertension in the elderly.